Motionsryttares nyttjande av ridning som friskvård - Lahtivuori, Malin (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2021)
In Sweden companies can give a specific amount of money to their employees for health-promoting activities. Some examples of health-promoting activities are swimming, dancing, golf, massage, gym and riding. All these activities are tax free if they are performed with the health-promoting allowance. There are some activities that are not considered health-promoting due to the fact that they might be expensive or time-consuming. Riding was added to the list of health-promoting activities in the beginning of 2018. The aim of the study was to find out How the health-promotion allowance for riding will be used. The question formulations where; How many people will this affect, which discipline is the most popular and what do the riders expect to get out of the riding as a health-promoting activity? There are yet no studies done on the subject. The study was conducted as a quantitative study using a questioner that was sent out via social media. The questioner got 358 responses of witch 98 % where from women and 2 % from men. The result indicates that the main reason for riding is the exercise (73 %) it proves the social aspect of riding also seem to be of great importance as 48 % of the respondents reported it to be the main reason why they ride. Nine percent of the respondents stated that for them riding is a “way to pass time”. Among the respondents 99% considered riding as a health-promoting activity. The health-promotion allowance will mostly get used by those who are over 41 years old (69 %), while of those under the age of 40 only 60 % will use the allowance on riding. The difference in use of the allowance between the ones with non-physical and physical work is only 3%. The health-promotion allowance will be used for training with a own horse by 59 % of the respondents, for training in a group at a riding school by 22 % of the respondents, for privet training at a riding school for 14% of the respondents and on ring charges by 5% of the respondents.